2011
DOI: 10.1007/978-94-007-2852-3_33
|View full text |Cite
|
Sign up to set email alerts
|

Prospects for Treating Foods with Cold Atmospheric Gas Plasmas

Abstract: In this review the potential applications of cold atmospheric gas plasmas are presented with particular reference to the problems of contamination of foods by biological agents. In addition to the accidental contamination of food, the very real threat arising from the deliberate contamination of the human food chain is also considered. The evidence that has been gained for the efficacy of cold plasmas in inactivating a wide range of biological agents is briefly surveyed. This is followed by an examination of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Several authors showed that non-thermal plasmas are able to inhibit different kind of fungi: food contaminant, clinical and phytopathogenic (Basaran et al., 2008; Sun et al., 2011; Daeschlein et al., 2014; Zhang et al., 2014; Dasan et al., 2016; Bartoš et al., 2017). As non-thermal plasma treatments are known to have multiple mechanisms of action, ranging from intracellular DNA fracture and protein degeneration to oxidation of the outer membrane of fungi (Moisan et al., 2001; Ma et al., 2004), the evolution of microbial resistance is enormously counteracted (Shama and Kong, 2012). On the other hand, studies carried out using different vegetal species have shown that seed treatment by cold plasmas is able to stimulate germination and seedling growth (Jiang et al., 2014; Ling et al., 2016; Jiayun et al., 2014; Stolarik et al., 2015; Ji et al., 2016; Meng et al., 2017; Zhang et al., 2017; Strejckova et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Several authors showed that non-thermal plasmas are able to inhibit different kind of fungi: food contaminant, clinical and phytopathogenic (Basaran et al., 2008; Sun et al., 2011; Daeschlein et al., 2014; Zhang et al., 2014; Dasan et al., 2016; Bartoš et al., 2017). As non-thermal plasma treatments are known to have multiple mechanisms of action, ranging from intracellular DNA fracture and protein degeneration to oxidation of the outer membrane of fungi (Moisan et al., 2001; Ma et al., 2004), the evolution of microbial resistance is enormously counteracted (Shama and Kong, 2012). On the other hand, studies carried out using different vegetal species have shown that seed treatment by cold plasmas is able to stimulate germination and seedling growth (Jiang et al., 2014; Ling et al., 2016; Jiayun et al., 2014; Stolarik et al., 2015; Ji et al., 2016; Meng et al., 2017; Zhang et al., 2017; Strejckova et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Plasma source, plasma feed gas and modes of application have a tremendous impact on the inactivation efficiency. Shama and Kong (2012) published a summary on plasma decontamination of foods, including bacon, pork, ham, apples, melons, mangos, lettuce, cheese, eggs and nuts. Furthermore, there have been recent studies on plasma treatment of corn salad (Baier et al, 2013), fresh fruits and vegetables (Schnabel et al, 2014), whole black pepper , and herbs and spices (Hertwig et al).…”
Section: Introductionmentioning
confidence: 99%
“…In this way, bulk properties are not affected. Furthermore, the multitude of inactivation mechanisms in plasma treatment counteracts the evolution of microbial resistance, which might emerge over time if only one inactivation mechanism is applied (Shama and Kong, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Rød et al (2012) reduced Listeria innocua contamination in sliced ready to eat (RTE) meat products. Misra et al (2011), and Shama and Kong (2012) proposed that non-thermal plasma techniques could reduce microorganism abundance in various foods, including pork, ham, fruit, eggs, and beans. Non-thermal plasma can also be used on wheat to remove bacteria, fungi, and insect pests, while also inactivating enzymes, and thus enhancing shelf life (Butscher et al, 2015(Butscher et al, , 2016.…”
mentioning
confidence: 99%